Análisis social, económico y ambiental de la productividad ganadera: uso óptimo de recursos - Jumbo Ordoñez, Dayana Elizabeth (Machala : Universidad Técnica de Machala, 2022)
The purpose of this research is to diagnose the social, economic and environmental factors that influence livestock productivity. The methodology applied is based on the compilation and analysis of bibliographic information contained in books, academic articles, national and international reports. In addition, this research considers a non-experimental, cross-sectional, argumentative and strategic design, obtaining information in questions directed to three farms, through a descriptive methodological outline with quantitative and qualitative variables. The results showed that 66.7% of livestock production is underutilized, with the highest concentration of this activity located in the Sierra region, below 80%. It was determined that the livestock sector has had a considerable contribution represented in last year's Gross Domestic Product (GDP) (8.2%). It is concluded that livestock productivity must be aligned with the objectives of sustainable development, which considers feasible alternatives to convert losses into profits, to generate profitability, stability and innovation, contributing to sustained and timely growth at the local and national levels and thus expand to international networks.
La presente investigación tiene como finalidad diagnosticar los factores sociales, económicos y ambientales que influyen en la productividad ganadera, la metodología aplicada se basa en la recopilación y análisis de información bibliográfica contenida en libros, artículos académicos, informes nacionales e internacionales. Además, esta investigación considera un diseño no experimental transversal, argumentado y estratégico, obteniendo información en preguntas dirigidas a tres haciendas, a través de un bosquejo metodológico descriptivo con variables cuantitativas y cualitativas. Los resultados reflejaron que la producción ganadera tendría poco aprovechamiento efectivo en un 66,7%, con la mayor concentración de esta actividad ubicada en la región Sierra, por debajo del 80%. Se determinó que el sector ganadero ha tenido un considerable aporte representado en el Producto Interno Bruto (PIB) del último año (8,2%). Se concluye que la productividad ganadera debe estar alineada a los objetivos de desarrollo sostenible, que considera alternativas factibles para convertir las pérdidas en ganancias, para generar rentabilidad, estabilidad e innovación aportando al crecimiento sostenido y oportuno a nivel local, nacional y así expandirse a redes internacionales.
Keywords: PECUARIA; HACIENDAS; SOSTENIBLE; MERCADO